Single-molecule fluorescence imaging techniques reveal molecular mechanisms underlying deoxyribonucleic acid damage repair - Kang, Yujin; An, Soyeong; Min, Duyoung; Lee, Ja Yil (Frontiers in Bioengineering and Biotechnology, 2022)
Advances in single-molecule techniques have uncovered numerous biological secrets that cannot be disclosed by traditional methods. Among a variety of single-molecule methods, single-molecule fluorescence imaging techniques enable real-time visualization of biomolecular interactions and have allowed the accumulation of convincing evidence. These techniques have been broadly utilized for studying DNA metabolic events such as replication, transcription, and DNA repair, which are fundamental biological reactions. In particular, DNA repair has received much attention because it maintains genomic integrity and is associated with diverse human diseases. In this review, we introduce representative single-molecule fluorescence imaging techniques and survey how each technique has been employed for investigating the detailed mechanisms underlying DNA repair pathways. In addition, we briefly show how live-cell imaging at the single-molecule level contributes to understanding DNA repair processes inside cells.